Is Mobitz type I atrioventricular block benign in adults? - Shaw, D B (Copyright 2004 by Heart, 2004)
Objective: To assess the need for pacing in adults with chronic Mobitz type I second degree atrioventricular block (Mobitz I). Design: Prospective study. Setting: District general hospital. Patients: 147 subjects aged ⩾ 20 years (age cohorts 20–44, 45–64, 65–79, and ⩾ 80) with chronic Mobitz I without second degree Mobitz II or third degree (higher degree) block on entry, seen from 1968 to 1993 and followed up to 30 June 1997. Sixty four had organic heart disease. The presence of symptomatic bradycardia was defined as highly likely in 47 patients (class 1); probable in 14 (class 2); and absent in 86 (class 3). Interventions: Pacemakers were implanted in 90 patients for the following indications: symptoms in 74 and prophylaxis in 16. Main outcome measures: The main outcome measure was death, with conduction deterioration to higher degree block or symptomatic bradycardia the alternative measure. Results: Five year survival to death was reduced in unpaced patients relative to that expected for the normal population (overall mean (SD) 53.5 (6.7)% v 68.6%, p < 0.001; class 3, 54.4 (7.3)% v 70.1%, p < 0.001). Paced patients fared better than unpaced (overall (mean (SD) five year survival 76.3 (4.5)% v 53.5 (6.7)%, p  =  0.0014; class 3, 87.2 (5.4)% v 54.4 (7.3)%, p  =  0.020; and organic heart disease, 68.2 (7.6)% v 44.0 (9.9)%, p ⩽ 0.0014). There were no deaths in the < 45 cohort. Survival to first outcome (main or alternative) was further reduced to 31.7 (5.0)% in 102 patients unpaced initially and 34.2 (5.7)% in class 3. Only the 20–44 cohort and patients with sinus arrhythmia had > 50% survival. Conclusion: Mobitz I block is not usually benign in patients ⩾ 45 years of age. Pacemaker implantation should be considered, even in the absence of symptomatic bradycardia or organic heart disease.